Techno-economic analysis of the co-gasification of sewage sludge and petroleum coke - Adeyemi, Idowu; Khan, Haider; Ghenai, Chaouki; Janajreh, Isam (Frontiers in Sustainability, 2023)
In this study, the co-gasification of sewage sludge and petroleum coke is assessed with equilibrium and numerical modeling. The gasification process of these binary wastes provides a potential pathway for waste management and environmental sustainability. The thermodynamic equilibrium approach is used first to calculate the maximum cold gasification efficiency (CGE) at different mixture ratios in an attempt to narrow down and focus on the appropriate mixing ratecomposition of the two feedstocks within the entrained flow gasifier. Furthermore, parametric study is conducted to show the gasification metrics, i.e., CGE and feedstock conversion, and the syngas composition at different gasification conditions. The equilibrium model is based on 8 unknowns in the gasification product namely: H2, CO, CO2, H2O, CH4, O2, Csolid and the temperature, under variable O2 and H2O molar ratios. Using three four elemental mass balance, fourthree equilibrium (Csolid) constant relations and energy balance, the mathematical model is developed. The model incorporates the solid un-burn carbon in the product species. The temperature of gasification is determined through an iterative process. Result of model shows that the maximum CGE is achieved when all the solid carbon is converted into the carbon monoxide with nearly all hydrogen present in the feedstock converted into the hydrogen gas. The maximum conversion was attained with sewage sludge and petroleum coke ratio of 1 at 1200 o C. The mole fraction of the syngas species obtained are XH2 = 0.4227, XCO = 0.5774, and small fraction of XCH4 = 0.0123. Moreover, the cold gasification efficiency (CGE) measures 87.02% for the H2 and CO syngas species and reached 91.11% for the three species, including CH4. Using this result, a highfidelity reactive flow model that accounts for the reactor geometry and the devolatilization kinetics is developed. This model accounts for an extended set of reactions covering the char combustion, water and gas shifts, Boudouard and devolatilization. Finally, economic analysis is carried out to assess the conditions when such process can be deemed to be profitable. The gasification of the sewage sludge and petroleum coke at 50:50 is economically viable at temperatures higher than 950 C...